The Influence of Training, Discipline and Work Motivation on the Employee Performance of Honda Workshop at PT. Indako Trading Coy Rantauprapat - Rakimen, Rakimen (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to examine and analyze the effect of training, discipline, and work motivation on the performance of Honda official workshop employees of PT Indako Trading Coy Rantauprapat. The research design used is library research and field research. The sample used in this study amounted to 37 respondents from 37 employees. The method used in this sampling is to use quantitative descriptive techniques. The data analysis method used is multiple linear regression analysis. Based on data analysis, the regression equation obtained is as follows: Y=11.345+0.015X1+ 0.295X2+0.282X3. The test result of the training variable has a positive and not significant effect on employee performance while discipline and motivation have a positive and significant effect on employee performance. F-test results show that all independent variables have a positive and significant effect on employee performance. Then, the correlation coefficient R-value of 0.759 means that there is a very strong and positive relationship between the three variables on employee performance. The coefficient of determination is 53.7% which means there is a relationship between the three variables while the remaining 46.3% is influenced by other variables outside the regression equation or variables that are not scrutinized. The researcher suggests to the official Honda workshop leader to continue to hold regular training for all workshop employees with the method of bringing the training center to the nearest area. Furthermore, the researchers suggest continuing to remind employees to always be creative and innovative in working with methods other than digital. Absence can be directly assessed in the form of neatness and cleanliness. Furthermore, researchers suggest continuing to build good communication relationships as well as maintaining and valuing work with the method of increasing salary regularly